Efficient liquid transport fabric for active sports (Indian Journal of Fibre & Textile Research (IJFTR), 2025)
This study designs an embossed jersey structure for fast liquid dissipation in highly active sportswear and workwear. Unlike conventional fabrics, where droplet diameter increases over time due to surface spreading, the newly designed fabric enables liquid absorption without lateral spreading, promoting efficient moisture evacuation. The structural parameters of polyamide 66 knitted fabrics are assessed for moisture transport in two forms: liquid and vapour. The comfort performance of the embossed structure is compared with simple jersey and interlock structures based on droplet kinetics and breathability. Droplet spreading behaviour is analysed through contact angle variation, droplet diameter, and droplet height as a function of time. Breathability is evaluated using water vapour permeability and air permeability measurements. The results show that the embossed jersey structure allows liquid dissipation without spreading, helping to prevent liquid diffusion and condensation. The jersey structure exhibits faster liquid wicking and higher water vapour and air permeability. Fabrics with higher porosity demonstrate superior breathability and moisture transport, contributing to improved physiological comfort.